Traffic medicine and road safety: The Australian perspective - Brian Fildes (570868) (2015)
International statistics show that Australia is one of the top 10 countries in terms of road crashes per 100,000 population. In spite of this, four people are killed and 90 seriously injured every day on Australian roads. In 2011, the Australian Transport and Infrastructure Council released a National Road Safety Strategy (NRSS) for Australia, calling for a reduction of at least 30 percent of deaths and serious injuries on our roads by the year 2020. The strategy is based on Safe System principles embracing the principle that in the longer term, no person should be killed or seriously injured on Australian roads. It accepts that people using the road network will inevitably make mistakes and that the road system must be more forgiving of these errors. It relies on better management of crash energy within the system to keep this within human tolerance. This adherence to what is generally known as Vision Zero aligns Australia with international best practice. To help achieve the immediate goal outlined in the strategy, a National Road Safety Action Plan (NRSAP) was recently adopted for the first three years from 2015 to 2017 focusing on four key areas – Safe Roads; Safe Speeds; Safe Vehicles; and Safe People. The action plan is focused on national efforts and activities to achieve long-term and permanent reductions in road trauma in line with the NRSS target. It aims to achieve these improvements through strategic investment in infrastructure and vehicle safety initiatives using best practice and capacity building as shown below: 1.Safe Roads: The plan calls for short- and long-term initiatives for road improvements based on best available evidence on road authorities at all government levels is necessary to ensure that Safe System principles are applied to all new road projects. 2.Safe Vehicles: Comprehensive regulatory and consumer tests are called for to ensure that proven safety design features and technologies are mandated in new Australian vehicles as quickly as possible. 3.Safe Speeds: Speed enforcement has been shown to be an effective management tool against speed-related crashes. The plan calls for a number of initiatives aimed at reducing speed-related risk. 4.Safe People: Various initiatives were outlined to improved driver and rider risk such as supervised learner driving hours, provisional licence periods, passenger night time restrictions, sanctions for speed and alcohol offences, and mobile phone bans. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.80